A reflection on COVID-19 and oral mucosal lesion: a systematic review - Kot, Wai Ying; Li, Jing Wen; Chan, Alice Kit Ying; Zheng, Li Wu (Frontiers in Oral Health, 2023)
Introduction The aim of this systematic review is to provide a clinical update of the current knowledge on COVID-19 and oral mucosal lesions, to analyze the types and prevalence of oral mucosal lesions in patients with COVID-19, and to clarify the potential association between COVID-19 and oral mucosal lesions. Methods The literature search was conducted using PubMed, Web of Science, Scopus and the Cochrane Library, as well as literatures via manual searches of the reference lists of included studies. Studies published in English that mentioned oral mucosal lesions in patients with COVID-19 were included, resulting in a total of 31 studies. Results Most of the included studies were considered to have a moderate to high risk of bias according to the Joanna Briggs Institute bias assessment tools. Based on COVID-19 severity, the characteristics and patterns of oral mucosal lesions in COVID-19 patients were described, analyzed and synthesized. Overall, ulcers without specific diagnosis had the highest prevalence in COVID-19 patients, followed by traumatic ulcers, candidiasis, petechiae and aphthous-like lesions. Homogeneity of data cannot be achieved in statical analysis, indicating randomness of outcome (ulcers without specific diagnosis, 95% CI: 28%–96%, I2 = 98.7%). Discussion Given the limited evidence from currently available studies, the association between COVID-19 and oral mucosal lesions remains difficult to clarify. Healthcare professionals should be aware of the possible association between COVID-19 and oral mucosal lesions, and we hereby discuss our findings.